Experimental cage culture of snow trout, Schizothorax richardsonii (Gray) and golden mahseer, Tor putitora (Hamilton) fry and fingerling in a sub-Himalayan lake Bhimtal, India - Basade, Yasmeen; Mohan, Madan (The Indian Journal of Animal Sciences, 2012)
Trials were conducted to ascertain the potential of cage culture in a sub- Himalayan lake for commercially important indigenous upland fishes. Growth performances of different grow-out stages, namely fry and fingerlings of snow trout, Schizothorax richardsonii and golden mahseer, Tor putitora were assessed for 3 months. Fishes were stocked @ 20 fish/ m3; one set of fishes (experimental) were fed a 40% crude protein (CP) extruded pelleted feed, while the other set (control) thrived on natural food present in the lake. Rate of survival, net weight gain, per cent weight gain, specific growth rate (SGR) and gross yield of snow trout and golden mahseer fry and fingerlings were significantly higher in experimental group compared to the control. Feed conversion ratio (FCR) was calculated only for the experimental groups. Thus, this simple practice offers the possibility of rearing fry and fingerlings of snow trout and golden mahseer in floating cages in the sub-Himalayan lakes by using extruded pelleted feed.